2017
DOI: 10.1080/00221325.2017.1279118
|View full text |Cite
|
Sign up to set email alerts
|

Family and School Influences on Youths' Behavioral and Academic Outcomes: Cross-Level Interactions between Parental Monitoring and Character Development Curriculum

Abstract: The authors examined the joint (interactive) roles of the Second Step curriculum (a validated social-emotional learning and bullying prevention program; Committee for Children, Seattle, WA) and parenting practices on students' behavioral and academic outcomes in Grades 5-8. Participants were 763 parents and their children from 22 schools (8 control and 14 treatment). A 2-level random coefficient model was conducted to assess the effect of parental monitoring on school outcomes, as well as the interaction betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…Likewise, adolescents are much more likely to react to environmental influences considering the uncertainty with new expectations and social life (63). Moreover, these findings are consistent with previous work, which has underscored the essential roles of school and family in developing child competency (64,65). Consistent with prior work [e,g., (66)], our findings document that family support and teacher support are associated with lower levels of delinquent behaviors in adolescents.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, adolescents are much more likely to react to environmental influences considering the uncertainty with new expectations and social life (63). Moreover, these findings are consistent with previous work, which has underscored the essential roles of school and family in developing child competency (64,65). Consistent with prior work [e,g., (66)], our findings document that family support and teacher support are associated with lower levels of delinquent behaviors in adolescents.…”
Section: Discussionsupporting
confidence: 89%
“…Students from welladjusted families will always have the tenacity to do their hardest, adapt, be more motivated, and take their involvement in the educational process seriously. This findings likely conform with previous ones suggesting that the family environment significantly influences student learning outcomes (Tanjung, 2020;Afriyani, 2020;Umar et al, 2020;Lindfors et al, 2018;García et al, 2018;Hampden-Thompson & Galindo, 2017;Top et al, 2017;Long & Pang, 2016;Jayanthi & Srinivasan, 2015;Cho & Campbell, 2011). Teachers/mentors and other people can affect student learning outcomes and motivation (Sacntrock, 2015).…”
Section: The Effect Of Family Environment On Learning Outcomessupporting
confidence: 90%
“…Regarding the explanation above, there is research that has contradictory results showing that the family environment has no relationship with student learning outcomes at school (Pappattu & Vanitha, 2017). While several other previous studies show the results of their research that there is a positive influence of the family environment on student learning outcomes Ion et al, 2020;Tanjung, 2020;Afriyani, 2020;Umar et al, 2020;Lindfors et al, 2018;Hampden-Thompson & Galindo, 2017;Top et al, 2017;Long & Pang, 2016;J. & K., 2015;Cho & Campbell, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…For example, Flouri and Midouhas (2016) found that school could not moderate the effect of family poverty on children's behavior in primary school. Overall, though, most of the studies found that the combined influences of these two factors could support the development of good behavior, emotional adjustment, well-being, and the prevention of delinquency among adolescents (Crespo, Jose, Kielpikowski, & Pryor, 2013;Davis et al, 2004;Lucero et al, 2015;Top, Liew, & Luo, 2017).…”
Section: Interaction Of School and Family Factorsmentioning
confidence: 99%